Synthetic Grey Water Treatment Through FeCl3-Activated Carbon Obtained from Cotton Stalks and River Sand - Mian Jawaduddin Pirzada; Sheeraz Ahmed Memon; Narain Das Bheel; Farhad Ali; Nisar Ahmed Gabol; Abdul Wahab Abro (Salehan Institute of Higher Education, 2019)
The research objective was to reclaim greywater through simple, easily available, and cost-effective methods. For this purpose, an activated charcoal was prepared from biomass (cotton stalk) through the pyrolysis process and sand collected from river Indus. Both materials were subjected to separate columns and applied as filters. Whereas, the efficiency of both materials as filter media was analyzed on the synthetic grey water (SGW). The formulation of synthetic greywater was a complicated process because the selection of ingredients and their amount should not exceed from the real grey water. So, for the presence of fecal contamination, a small amount (10 ml L-1) of settled sewage was added to the distilled water, while to mimic the organic load, several chemical products of technical grade were also added. The physicochemical and microbiological characteristics of this SGW were tested before and after treatment. The results show that both mediums (AC and river sand) were very effective in the greywater treatment. The removal efficiency for BOD and COD was up to 91.2%, and 70% respectively. Similarly, the removal measure for turbidity was 91.3%. While the pH showed that the synthetic grey water was alkaline in nature with a value of 10 because the washing detergents used during the preparation of SGW, but after passing through both filter columns, pH was observed in between 7 and 8 units. Furthermore, the removal value examined after passing SGW from both columns for total coliforms was 46.87 CFU/100 ml from1500 CFU/100 ml.